2005
DOI: 10.1258/002221505774481291
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical complications of the second 100 adult cochlear implant patients in Birmingham

Abstract: One hundred consecutive adult cochlear implant patients, numbered 101 to 200 in an ongoing series, were prospectively monitored and data collected using the same protocol as for the first 100 patients. The study period was 1999 to 2001. The total number of procedures was 122. Changes in practice following the first 100 implants included a standard surgical technique with a smaller incision and lesser flap mobilization, and routine facial nerve monitoring. As far as was practicable, the same commercial type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 3 publications
4
38
1
2
Order By: Relevance
“…Nevertheless, the surgical procedure may be expected to have a risk of deafness similar to stapedectomy [Shea, 1998;Häusler, 2000] or cochlear implantation [Green et al, 2004;Dutt et al, 2005]. In our patients, hearing thresholds were in an order of magnitude that approached those of cochlear implant candidates.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, the surgical procedure may be expected to have a risk of deafness similar to stapedectomy [Shea, 1998;Häusler, 2000] or cochlear implantation [Green et al, 2004;Dutt et al, 2005]. In our patients, hearing thresholds were in an order of magnitude that approached those of cochlear implant candidates.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with otosclerosis as a recognized cause of vestibular complaints, four patients experienced vertigo prior to the surgery [14,15] . However, two patients had postoperative vertigo, which was clearly related to the surgery, one of which was due an unintentional lesion of the vestibule during the operation.…”
Section: Discussionmentioning
confidence: 90%
“…Vertigo is a common complication of CI [7,11,14] . Consistent with otosclerosis as a recognized cause of vestibular complaints, four patients experienced vertigo prior to the surgery [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…Excluding device-related complications and facial palsy, migration-extrusion of the implant body and flapwound problems are the major complications of cochlear implant surgery. In their cochlear implantation series, Dutt et al [18] reported complications of flap breakdown (1.6%), extrusion of electrode array (0.8%) and device failure (0.8%). Migirov et al [19] found that the main reason for revision surgery was device failure followed by woundflap complications for cochlear implant surgery.…”
Section: Discussionmentioning
confidence: 99%